Biodegradation of Heavy Oil with High Asphaltene Content by Kocuria sp. - Huang, Taipeng; Chen, Jing; Yang, Qiuyan; Zhang, Yongkui; Ding, Ranfeng (Asian Journal of Chemistry, 2012)
Heavy oil biodegradation capacity of Kocuria sp. isolated from the oil contaminated soil of Tuha oil field in west China was tested at an orthogonal experiment, which showed that the best biodegradation conditions were as following: pollution intensity (PI) 3 %, initial pH 7.0, C:N ratio 100:3 and C:P ratio 100:0.8. Pollution intensity played a main role on the biodegradation. Under the best conditions, the heavy oil from Tuha oil field (viscosity 30 Pa·s at 50 ºC and density 0.9962 g/cm3 at 90 ºC) and asphaltene from it was degraded 43.26 % and 55.84 % respectively, within 7 days in laboratory. Furthermore, through analyzing changes of crude oil components by a gas chromatography and mass spectrum, the strain could cause significant changes of organic fractions in the oil.